Coordination crosslinking of helical substituted oligoamide nanorods with Cu(II). Issue 3 (3rd March 2020) - Buchanan, Claire; Garvey, Christopher J; Puskar, Ljiljana; Perlmutter, Patrick; Mechler, Adam
ABSTRACT: Substituted oligoamides are short sequences of unnatural amino acids. Oligoamides made entirely of β 3 amino acids yield helical monomers that, if N-acylated, assemble into nanorod structures via a supramolecular assembly motif. In this work, coordination crosslinking was used to create complex nanomaterials from oligoamides WKLWEL (KE) and WELWEL (EE) (the letters denote the analogous α-amino acids). Upon Cu(II) addition, atomic force microscopy and small angle neutron scattering revealed morphologic changes specific to KE but absent in EE. Vibration spectroscopy measurements revealed that Cu(II) can coordinate to the amine moieties of the side chains, without direct effect on the backbone amides. While coordination in excess solvent lead to regular nanostructures, fast drying of the sample yielded oligoamide templated crystallization of CuCl2 . The metal coordination crosslinking of supramolecular assemblies as reported here is the first realization of a metallosupramolecular framework structure. Graphical Abstract: